Changes in abdominal profiles of Greenland White-fronted Geese during spring staging in Iceland - Boyd, Hugh; Fox, Anthony D; Kristiansen, Jens N; Stroud, David A; Walsh, Alyn J; Warren, Stephanie M (Wildfowl, 1998)
Abdominal profiles of spring-staging White-fronted Geese in Iceland were recorded in 1990, 1991, 1997 and 1998, chiefly at Hvanneyri, the largest known staging area. Median profile scores were markedly lower on arrival in Iceland than at departure from Ireland in the same spring. Median profile scores and the proportions of fat geese increased from arrival (16-24 April) to departure (by 12 May), though profiles of some individually-marked birds did not increase. Most of the increase in median scores in 1997 and 1998 occurred before the end of April, whereas most occurred after that time in 1990 and 1991. Median scores in mid-April were generally higher in 1990 and 1991 than in 1997 or 1998, but those in May were higher in 1997 and 1998 than in 1990 and 1991. Median scores from paired females started higher than males and increased more rapidly and pairs with broods tended to have larger profiles than those without. In 1998, other adults, confirmed or presumed to be offspring from earlier years, accompanied about 5% of pairs. These pairs, and the adults' accompanying them, also tended to have larger profiles than pairs without young. The median profile scores of females feeding on swards dominated by Meadow- grass Poa pratensis increased more rapidly than those on Tufted hair-grass Deschampsia caespitosa, though those of male did not. Many geese apparently left for west Greenland with relatively little abdominal fat.